Genomic islands of differentiation in two songbird species reveal candidate genes for hybrid female sterility. Issue 4 (26th February 2018) - Mořkovský, Libor; Janoušek, Václav; Reif, Jiří; Rídl, Jakub; Pačes, Jan; Choleva, Lukáš; Janko, Karel; Nachman, Michael W.; Reifová, Radka
Abstract: Hybrid sterility is a common first step in the evolution of postzygotic reproductive isolation. According to Haldane's Rule, it affects predominantly the heterogametic sex. While the genetic basis of hybrid male sterility in organisms with heterogametic males has been studied for decades, the genetic basis of hybrid female sterility in organisms with heterogametic females has received much less attention. We investigated the genetic basis of reproductive isolation in two closely related avian species, the common nightingale ( Luscinia megarhynchos ) and the thrush nightingale ( L. luscinia ), that hybridize in a secondary contact zone and produce viable hybrid progeny. In accordance with Haldane's Rule, hybrid females are sterile, while hybrid males are fertile, allowing gene flow to occur between the species. Using transcriptomic data from multiple individuals of both nightingale species, we identified genomic islands of high differentiation ( F ST ) and of high divergence ( D xy ), and we analysed gene content and patterns of molecular evolution within these islands. Interestingly, we found that these islands were enriched for genes related to female meiosis and metabolism. The islands of high differentiation and divergence were also characterized by higher levels of linkage disequilibrium than the rest of the genome in both species indicating that they might be situated in genomic regions of low recombination. This study provides one of the first insights into genetic basis of hybrid female sterility in organisms with heterogametic females.